1994
DOI: 10.1093/intimm/6.3.409
|View full text |Cite
|
Sign up to set email alerts
|

Some antioxidants inhibit, in a co-ordinate fashion, the production of tumor necrosis factor-α, IL-β, and IL-6 by human peripheral blood mononuclear cells

Abstract: Some antioxidants, including butylated hydroxyanisole (BHA), tetrahydropapaveroline (THP), nordihydroguiauretic acid, and 10,11-dihydroxyaporphine (DHA), were found to be potent inhibitors of the production of tumor necrosis factor (TNF)-alpha, IL-1 beta, and IL-6 by human peripheral blood mononuclear cells (PBMC) stimulated by lipopolysaccharide (LPS) (IC50s in the low micromolar range). Inhibition of cytokine production was gene selective and not due to general effects on protein synthesis. Inhibition of cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(50 citation statements)
references
References 0 publications
3
45
0
1
Order By: Relevance
“…Substantial evidence exists supporting the concept that antioxidants, including synthetic and natural products, suppress cytokine production by monocytes/macrophages (20,32). These previous papers indicate that ROIs play an important role in LPS-induced cytokine production.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Substantial evidence exists supporting the concept that antioxidants, including synthetic and natural products, suppress cytokine production by monocytes/macrophages (20,32). These previous papers indicate that ROIs play an important role in LPS-induced cytokine production.…”
Section: Discussionmentioning
confidence: 92%
“…Riboprobe syntheses was driven by the T7 bacteriophage RNA polymerase with [␣-32 P]UTP as the labeling nucleotide. 32 P probe (6 ϫ 10 5 cpm/sample) was added to tubes containing the sample RNA (4 g), which was dissolved in 8 l of hybridization buffer. The samples were heated to 90°C, the temperature slowly decreased to 56°C, and then incubated overnight.…”
Section: Rna Preparation and Rnase Protection Assay (Rpa)mentioning
confidence: 99%
See 1 more Smart Citation
“…Although Ro106-9920 does have activity against 5-lipoxygenase and inducible nitric-oxide synthase, zileuton, an inhibitor of 5-lipoxygenase, does not inhibit TNF␣ production in PBMNs (40), and endogenous nitric oxide decreases TNF␣ in rat models of hepatic ischemia-reperfusion (41).…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that ROI may be not only part of an antimicrobial defense mechanism but may also be involved in signal transduction of immunoregulatory processes [3,4]. For instance, ROI have been shown to induce the expression of cytokines [5][6][7], adhesion molecules [8,9] and proto-oncogenes [10,11]. We and others have demonstrated that gene expression in response to ROI can be attributed to the activation of certain transcription factors including NF-xB and AP-1, both of which are activated under prooxidant conditions [12][13][14].…”
Section: Introductionmentioning
confidence: 99%